AI DISCLOSURE IMPROVES BANKING MARKET PERFORMANCE IN INDONESIA AND THE ROLE OF BANK AGE AS A VARIABLE AFFECTING PROFITABILITY AND PROFIT GROWTH - Ossi Ferli; Erric Wijaya; Oktavia Ramadaniyah; Zhafira Ramadhani; Ratna Nilanjana Kurniathena (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the effect of disclosure of the use of Artificial Intelligence (AI) technology in annual reports on the financial performance of banks listed on the Indonesia Stock Exchange in the period 2020-2024. Using a quantitative approach and panel data regression method, this study evaluates the relationship between the frequency of disclosure of AI-related terms (AIFREC) and financial performance indicators such as Return on Equity (ROE), Net Interest Income (NII), Price to Earning (P/E) and Total Expenses (TEXP). The results show that the frequency of AI disclosure has a significant impact on market perception (P/E ratio), and negatively affects ROE but positively affects market value. In addition, internal bank characteristics such as asset size, proportion of independent board, and bank age also influence the level of AI disclosure. This study emphasizes the importance of transparency and communication strategies in the adoption of AI technology as part of the digital transformation of the banking sector, and encourages the need for more uniform AI reporting standards to increase investor confidence and operational efficiency.